Coordinated operations of multiple-reservoir cascaded hydropower plants with cooperation benefit allocation. (15th June 2018) - Shen, Jianjian; Cheng, Chuntian; Zhang, Xiufei; Zhou, Binbin
Abstract: The coordinated operations of multiple-reservoir cascaded hydropower plants provide opportunities to increase the benefits of the entire river system. However, it is very challenging to fairly allocate the incremental benefits of cooperation among all participant hydropower plants, which is critical to the implementation of operation polices in practice. A methodology that combines POA-DDDP–based multidimensional search algorithm(PDMSA) with game theory is proposed to address this challenge. The PDMSA is developed to determine optimal operation decisions and obtain the multi-yearly average revenue under all possible coalitions of plants. Thus, the cooperation benefit can be accurately calculated based on the differences of generation production revenue among various coalitions. The game-theoretic Shapley method is used to find the appropriate share of each cooperating plant from overall cooperation benefits. The cooperative core based on a set of necessary conditions helps select possibly stable allocation schemes, and their stability is evaluated by the propensity to disrupt(PTD). The proposed methodology is applied to a multiple-reservoir hydropower system on Lancang River, which is one of 14 large hydropower bases in China. This case shows that the method provides the most stable incremental allocation scheme by comparison with several commonly used methods. Highlights: The coordinated operations with benefit allocation originate from actual demands. An integrated methodology that combines PDMSA with game theory is proposed. Benefit allocation among plants is made by Shapley method and evaluated by PTD. This method is applied to a multiple-reservoir hydropower system on Lancang River. The method produces the most stable allocation scheme compared to other methods.